Pendampingan dalam Pengenalan dan Praktik SADARI untuk Kesehatan Payudara - Pitria; Natalia, Omiati (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Mastalgia, or breast pain, is a common complaint frequently experienced by women, particularly those of reproductive age. Mastalgia is divided into two types: cyclic and non-cyclic. Non-cyclic mastalgia is harder to identify its exact cause and can disrupt the quality of life and mental health of women. The global prevalence ranges from 47-70%, with around 60-65% of women in Indonesia having experienced it. At Pringgarata Health Center in Central Lombok, approximately 15-20% of reported breast health complaints are pain without a clear cause, which is suspected to fall under non-cyclic mastalgia. One preventive measure that can be taken is educating women about self-breast examination (SADARI). This education is expected to raise awareness about the importance of early detection and reduce anxiety related to breast health issues. This study uses a qualitative approach with a descriptive method to describe the implementation of SADARI education at Pringgarata Health Center. The research subjects are women of reproductive age who receive education and practice SADARI. The results show an increase in the participants' understanding and skills in performing SADARI. It is recommended that this education be continued to increase public awareness, especially in rural areas, about the importance of early detection of non-cyclic mastalgia.